2006
DOI: 10.1080/14786410500510849
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis of the essential oil of Achillea millefolium L. from various European Countries

Abstract: Variations in the essential oil composition of Achillea millefolium L. growing in Estonia and in other European countries, were determined. The oils were obtained in yields of 0.9-9.5 mL kg-1. A total of 102 components were identified. The quantitatively most important components of yarrow were sabinene, beta-pinene, 1,8-cineole, artemisia ketone, linalool, alpha-thujone, beta-thujone, camphor, borneol, fenchyl acetate, bornyl acetate, (E)-beta-caryophyllene, germacrene D, caryophyllene oxide, beta-bisabolol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 7 publications
4
36
0
Order By: Relevance
“…Both in publications reviewed therein, and in later publications (notably, Orav et al 2006), considerable variation of chemotypes within A. millefolium is reported. In older literature, chemists generally did not provide adequate taxonomic information or cite voucher specimens that would allow the exact nature of study materials to be independently determined; therefore, some of the reported infrataxon variability in chemical content and bioactivity was probably due to the failure to distinguish between subspecies or species of the A. millefolium complex (Chandler et al 1982;Guédon et al 1993).…”
Section: Ethnobotany and History Of Usementioning
confidence: 89%
“…Both in publications reviewed therein, and in later publications (notably, Orav et al 2006), considerable variation of chemotypes within A. millefolium is reported. In older literature, chemists generally did not provide adequate taxonomic information or cite voucher specimens that would allow the exact nature of study materials to be independently determined; therefore, some of the reported infrataxon variability in chemical content and bioactivity was probably due to the failure to distinguish between subspecies or species of the A. millefolium complex (Chandler et al 1982;Guédon et al 1993).…”
Section: Ethnobotany and History Of Usementioning
confidence: 89%
“…10 Borneol is a monoterpene commonly isolated from plants of different genera. [11][12][13] Borneol can also be produced by the reduction of camphor, which is used in traditional medicine for analgesia and anesthesia. In addition, this compound inhibits rat bone resorption 14 , by inhibiting the formation of osteoclasts 15 , and causes microtubule depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Achillea millefolium was studied by GC [26][27][28][29][30][31][32], therewith this herb was a component of an elixir [26]. Orav et al [28] compared the compositions of the essential oils of Achillea millefolium collected in different European countries.…”
Section: Herbal Drug Raw Materials and Herbal Mixturesmentioning
confidence: 99%